Implementation of REST API in Web Service System for Medical Resume Provision - Roziqin, Mochammad Choirur; Noor, Muhammad Syeikhoni; Iskandar, Abdullah; Yuliantika, Ananda (International Journal of Healthcare and Information Technology, 2023)
This research seeks to develop a web service system that functions as a medical resume provision via RESTful API. Accurate and comprehensive medical records are critical in the identification and diagnosis of patients. Medical resumes, which summarize a patient's healthcare services and are completed by the responsible doctor, are an essential component of medical records. Electronic medical record systems can aid in patient care, and a patient's prior health history is crucial in developing a holistic and continuous treatment plan. Unfortunately, patients often require a fresh medical examination due to a lack of past health data. The proposed system can interconnect with other electronic medical record systems and facilitate the exchange of medical resume data between hospitals. This research employs the waterfall development system. The resultant system provides patient medical resumes from participating hospitals, offering a solution to the problem of inconsistent patient information and clinical data, and improves service quality and diagnosis accuracy based on available data.